2023
DOI: 10.1002/ctm2.1346
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell transcriptome sequencing of B‐cell heterogeneity and tertiary lymphoid structure predicts breast cancer prognosis and neoadjuvant therapy efficacy

Abstract: BackgroundBreast cancer (BC) is a highly heterogeneous disease, and although immunotherapy has recently increased patient survival in a number of solid and hematologic malignancies, most BC subtypes respond poorly to immune checkpoint blockade therapy (ICB). B cells, particularly those that congregate in tertiary lymphoid structures (TLS), play a significant role in antitumour immunity. However, B‐cell heterogeneity at single‐cell resolution and its clinical significance with TLS in BC need to be explored furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 57 publications
(116 reference statements)
0
4
0
Order By: Relevance
“…The structural, molecular, and topographical heterogeneity of TLS has been demonstrated in other types of malignancies, such as renal cancer [ 20 ], breast cancer [ 21 ], and oral cancer [ 22 ]. The majority of lesions in this study were squamous cell carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…The structural, molecular, and topographical heterogeneity of TLS has been demonstrated in other types of malignancies, such as renal cancer [ 20 ], breast cancer [ 21 ], and oral cancer [ 22 ]. The majority of lesions in this study were squamous cell carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains an open question whether the predictive value of TLS is exclusive to ICIs or extends to predicting sensitivity to neoTx, particularly in LARC patients. In breast cancer, four studies have demonstrated a significant association between TLS and the efficacy of neoadjuvant chemotherapy 31 34 . In the NT cohort, TLS was observed in 98.3% of cases.…”
Section: Discussionmentioning
confidence: 99%
“… 119 Using single‐cell transcriptome sequencing, Wang et al. 120 identified CD23 as a biomarker of TLS in BC and proposed that heterogeneity of B cells in TLS determines the efficacy of immunotherapy. DC heterogeneity has also been of concern, and investigators determined that the functional status of CCL19‐expressing DCs correlated with favorable anti‐PD1 responses, T‐cell immunity, and the presence of TLS.…”
Section: Role Of Tls In Cancermentioning
confidence: 99%